2020
DOI: 10.1016/j.omega.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft routing and crew pairing: Updated algorithms at Air France

Abstract: Aircraft routing and crew pairing problems aims at building the sequences of flight legs operated respectively by airplanes and by crews of an airline. Given their impact on airlines operating costs, both have been extensively studied for decades. Our goal is to provide reliable and easy to maintain frameworks for both problems at Air France. We propose simple approaches to deal with Air France current setting. For routing, we introduce a compact MIP formulation that can be solved by current MIP solvers in at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 46 publications
(45 reference statements)
0
16
0
1
Order By: Relevance
“…It was also used tried for crew pairing. Column generation pricing subproblem within a new resource constrained shortest path framework was also modelled [20]. Later, it was also suggested that to enable Air Traffic Controllers to control and supervise traffic with ease, flight traffic is carried out on set of predefined routes that have very low number of intersections.…”
Section: Methodsmentioning
confidence: 99%
“…It was also used tried for crew pairing. Column generation pricing subproblem within a new resource constrained shortest path framework was also modelled [20]. Later, it was also suggested that to enable Air Traffic Controllers to control and supervise traffic with ease, flight traffic is carried out on set of predefined routes that have very low number of intersections.…”
Section: Methodsmentioning
confidence: 99%
“…If the number of such columns together with those generated when the linear relaxation is solved is not too big, then an off-the-shelf solver can be used. This strategy has been recently used by Cacchiani and Salazar-González [2017] and Parmentier and Meunier [2020] for airline scheduling and crew pairing problems.…”
Section: Methods For Solving the Problemmentioning
confidence: 99%
“…The general approach in these studies is to use the exact methods that will provide the solution in a short time for small-scale problems prevailing integrated approach, the heuristic approach is used to check whether better solutions than those obtained in the sequential approach can be found. Parmentier and Meunier [13], Mohamed et al [12], and Mohamed et al [14] are other studies seeking integrated solutions to AMR and Crew Scheduling in problems with a weekly time horizon.…”
Section: Solution Methodsmentioning
confidence: 99%
“…Diaz-Ramirez et al[9], Weide et al[10], Dunbar et al[11], Mohamed et al[12], Parmentier and Meunier[13], Mohamed et al[14], Ahmed et al[15] √ √ Lacasse-Guay et al[16], Papakostas et al [17], Yang and Yang [18], Maher et al [19], Liang et al [20], Başdere and Bilge [21], Irvine et al [22], Gopalan [23], Al-Thani et al [24], Safaei and Jardine [25], Qin et al [26], Sarhani et al [27], Eltoukhy et al [28], Orhan et al [29], Aslamiah et al [30], Afsar et al [31], Kim et al [32], Bulbul and Kasımbeylı [33], Zhong et al [34], Afia and Sarhani [35], Zhang [36], Eltoukhy et al [37], Cui et al [38], Eltoukhya et al [39] √ Vos et al [40], Zhang et al [41], Dožic et al [42], Liu et al [43], Hu et al [44], Jufri et al [45], Lin and Wang [46] √ Akartunalı et al [47], Akartunalı et al [48], Burke et al [49], Chen et al [50], Sun [51], Jiang and Barnhart [52], Abdelghany et al [53], Sandamali et al [54], Zhao et al [55], Peng et al [56], Chen et al [57], Wang and Zhang [58], Ahmadian et al [59] √ Azadeh et al [60], Deng and Lin [61], Ionescu and Kliewer [62], Dück et al [63], Saddoune et al [64], Suraweera et al [65], Bayliss et al [66], Kasirzadeh et al [67], Lijima and Nishi [68], Arayikanon and Chutima [69] √ Özdemir et al [70], Pilla et al [71], Kang et al [72], Yang et al [73], Ma et al [74], Raudasoja [75], Boudia et al [76], Liu et al [77], Dozic et al [78], Note: EA: Ergonomic Assessment; MP: Maintenance Personnel; MTIS: Maintenance Tracking Info Systems; SI: Safety Issues; SRP: Schedule Recovery Problem…”
mentioning
confidence: 99%